The middle - piece agenesis of spermatozoa: A defect of spermiogenesis - Silva, Jorge Fonseca da; Moraes, José Carlos Ferrugem; Schuch, Luís Henrique (Pesquisa Agropecuaria Brasileira, 2014)
A Hereford bull examined through clinical exam and spermiogram, presented high percentage of some sperm defect, the non-development of the middle-piece and tail of spermatozoa. An exhaustion test was done for differential diagnosis; probably the bull was patient of an arrested spermiogenesis. According to this report, for the determination of ion concentration of epididymal plasm, further studies with electron microscopy and some investigations as to the inheritance of the process, were suggested.